Evaluation of Cost Performance In The Surabaya-Gempol Toll Road Reconstruction Project Using Schedule Variance (SV) and Cost Variance (CV) Analysis - Hamzah, Aulia; Teki Tjendani, Hanie; Witjaksana, Budi (Pelopor Publikasi Akademika, 2025)
The reconstruction of the Surabaya-Gempol Toll Road underscores the critical role of effective project management in large-scale infrastructure projects, particularly in ensuring time and cost efficiency. This study employs the Earned Value Method (EVM) to evaluate project performance through the analysis of Schedule Variance (SV) and Cost Variance (CV). These indicators provide a comprehensive assessment of the project's adherence to its planned schedule and budget. The findings reveal that the project faced initial schedule delays due to logistical and technical challenges, resulting in negative SV values during the early weeks. These delays were primarily caused by weather conditions, late material deliveries, and coordination issues among project stakeholders. However, corrective measures, including extended working hours, additional labor deployment, and optimized scheduling, successfully addressed these issues, leading to positive SV values towards the end of the project. The CV analysis highlighted consistent cost efficiency throughout the project. Positive CV values dominated the majority of the timeline, reflecting effective cost control and resource management. Despite minor cost deviations due to unanticipated repairs and equipment maintenance, the project demonstrated an ability to maintain overall financial performance within the budget framework. This study emphasizes the significance of data-driven decision-making and proactive variance management in achieving project goals. By leveraging SV and CV analyses, infrastructure projects can better anticipate potential issues, implement timely corrective actions, and improve overall performance. The results of this research offer valuable insights for managing similar large-scale projects, contributing to enhanced efficiency and sustainable development in Indonesia's infrastructure sector.